C‐Met function requires n‐linked glycosylation modification of pro‐Met12. Issue 4 (18th February 2013) - Chen, Run; Li, Juan; Feng, Chun‐Hong; Chen, Shao‐Kun; Liu, You‐Ping; Duan, Chun‐Yan; Li, Hong; Xia, Xian‐Ming; He, Tao; Wei, Mei; Dai, Rong‐Yang
Abstract c‐Met, the receptor for hepatocyte growth factor (HGF), is cell surface tyrosine kinase that controls cancer cell growth, survival, invasion, and metastasis. Post‐translational modification, such as glycosylation, plays an essential role in regulating the function of cell surface molecules. Whether glycosylation modification regulates the enzymatic properties of c‐Met is unknown. In this study, we investigated the effect of glycosylation on the function of c‐Met. We found that c‐Met is an N‐linked glycosylated protein. Both pro‐Met and p145Met (the β subunit of mature c‐Met) have N‐linked glycosylation. Glycosylation inhibitor studies revealed that the N‐glycosylation modification of p145Met is from pro‐Met, but not due to the further modification of pro‐Met. Importantly, blocking the N‐glycosylation targets pro‐Met to cytoplasm and initiates its phosphorylation independent of HGF engagement. Nonglycosylated pro‐Met activates c‐Met downstream pathways to a certain extent to compensate for the degradation of p145Met induced by glycosylation blocking‐mediated endoplasmic reticulum (ER) stress. J. Cell. Biochem. 114: 816–822, 2013. © 2012 Wiley Periodicals, Inc.